Partisipasi Masyarakat Lokal Dalam Pengembangan Pariwisata Wahana Air Di Pangandaran - Tiara Maharani Ashaf; Annisa Inayaturrahmah Choiri Putri; Salma Luthfiyah Assegaf; Dede Tresna Wiyanti (Badan Riset dan Inovasi Nasional (BRIN), 2025)
The tourism industry is experiencing very rapid development in various countries. The tourism industry is a very important economic sector that is able to increase labor opportunities. Pangandaran Regency is known for its beach destination, popular among local and foreign tourists. Watersports are defined as sports that use water as its main medium and can be categorized as recreational tourism. This research aims to look at community-based tourism management in watersport establishments on the East Coast of Pangandaran. This research uses descriptive qualitative research methods. Withdrawing informants using purposive sampling technique. The number of research informants were 6 people, namely the administrators of the Komunitas Wahana Air Pangandaran (KWAP), managers/owners and crews. Data collection techniques in this research are observation, in-depth interviews, and literature study. The research results show that the local community participates in watersport tourism in Pangandaran. Their involvement includes providing watersport services for tourists. Water tourism on the East Coast of Pangandaran is the most popular type of water tourism. This research found that watersports on the East Coast of Pangandaran have demonstrated community-based tourism management with the active participation of local communities. The practice of watersport tourism in Pangandaran fulfills four characteristics of local community-based tourism development, namely: small business scale, community acceptance, community participation, and local participation culture. Community participation can be seen in various forms, such as the manpower, knowledge and expertise of the crew and watersport managers.